Social Skills in Early Childhood and Primary Schools: A Systematic Review - Salimi, Moh; Fauziah, Muna (Jurnal Ilmiah Peuradeun, 2023)
This study aimed to summarize studies on early childhood and elementary school social skills and identify research gaps. The study used a systematic literature review method. A total of 50 articles on early childhood and elementary school social skills were published over the past ten years, from 2013 to November 2022. The 50 articles were the subject of the study. Nine thousand one hundred fifty samples comprise 1,958 early childhood and 7,192 elementary school students. The data were collected by studying documentation of several previous articles through database searches such as Google Scholar, scopus.com, ERIC, Sage Publication, Science Direct, and Taylor and Francis. The data analysis techniques were quantitative (statistical) and qualitative (descriptive). This study indicated that 50 articles had highlighted social skills in early childhood and elementary school that had successfully improved through the implementation of learning outside the classroom revealing the attitudes such as cooperation, assertion, responsibility, and self-control in students, and intellectual abilities, language, Education, computers, gender, and parental support. This study is helpful for educators as material for maximizing social skills. A systematic literature review of students' social skills factors is recommended for future researchers.